Induction of oxidative stress by paradoxical sleep deprivation in different body organs of rats - Iman M. Mourad; Heba M. Fahmy (International Journal of Pharma and Bio Sciences, 2017)
Sleep deprivation is thought to be a risk factor for several diseases. The aim of the present study is to investigate the effect of paradoxical sleep deprivation for 48 h on different body organs in male albino rats. The data revealed a significant increase in lipid peroxidation levels in the heart, liver, and testis of sleep-deprived animals. Reduced glutathione content recorded a significant decrease in the cardiac and hepatic tissues after 48 hours of sleep deprivation, while non significant effects were obtained in both testicular and renal tissues. The hepatic catalase activity showed a significant decrease, while the changes in cardiac, testicular and renal catalase activities were non-significant. Sleep deprivation also induced a significant decrease in cardiac and renal superoxide dismutase activity. Conversely, a non significant increase in the enzyme activity was recorded in the hepatic and testicular tissues. Regarding nitric oxide level a significant decrease was recorded in the heart. However, a significant increase was obtained in the liver and testis. The renal nitric oxide level showed nearly no change from control. We concluded that sleep deprivation for 48 h could induce oxidative stress in the cardiac, hepatic and testicular tissues of male albino rats and it has no effect on renal tissue.